RNA-seq analysis reveals a positive role for NGF in the myogenic differentiation of bovine skeletal muscle satellite cells - Li, Xin; Zhao, Zhongli; Cao, Yang; Zhao, Yumin; Qin, Lihong (Frontiers in Genetics, 2026)
In this study, we successfully isolated and cultured bovine skeletal muscle satellite cells (bSMSCs) and induced muscle cell formation in vitro. Skeletal muscle satellite cells (SMSCs) were isolated from the deep tissues of foetal bovine hind limbs and differentiated with 2% horse serum in vitro. The transcriptome sequencing results revealed a total of 1030 differentially expressed genes (DEGs) in the middle stage of differentiation (day 3) compared with the predifferentiation stage (day 0). A total of 374 DEGs were identified in the postdifferentiation stage (day 7) compared with the middle differentiation stage (day 3). We further investigated the regulatory effects of the DEG nerve growth factor (NGF) on the proliferation and myogenic differentiation of bSMSCs. The overexpression of NGF increased the mRNA and protein expression levels of myosin heavy chain (MyHC) and myogenin (MyoG), which are myoblast development markers, whereas NGF knockdown had the opposite effect; however, NGF did not affect the expression of the proliferation marker paired box gene 7 (Pax7) in bSMSCs. In addition, functional enrichment analysis of the DEGs revealed that the PI3K/Akt signalling pathway was significantly enriched in the DEGs and that NGF regulates myogenesis through the activation of the PI3K/Akt signalling pathway. Our results revealed that NGF was shown to be a putative regulator that controls myogenesis by activating the PI3K/Akt signalling pathway. The study provided a reference for further studies on the molecular mechanism of myogenic differentiation, regulatory network establishment, and beef quality improvement.